Officina di IG XIV2 – Bracieri inediti da Taranto - De Blasio, Teresa Sissy (Axon)
This paper examines some unpublished braziers, currently stored at the National Archaeological Museum of Taranto. Three of them are inscribed with the same anthroponym in the genitive case (Ἑκαταίου), while the remaining eight are anepigraphic. Braziers, which were used both in daily life and as domestic furnishings, were widely distributed throughout the Mediterranean during the Hellenistic period. These new findings further confirm the involvement of Taranto, along with some other Italian cities, in the trade and circulation of these objects throughout the Mediterranean area. This paper aims to provide an overview of this phenomenon, with a particular focus on the identity of Hekataios and the characteristics of his production.